Disruption of circadian rhythm by alternating light‐dark cycles aggravates atherosclerosis development in APOE*3‐Leiden.CETP mice. Issue 1 (10th October 2019) - Schilperoort, Maaike; van den Berg, Rosa; Bosmans, Laura A.; van Os, Bram W.; Dollé, Martijn E. T.; Smits, Noortje A. M.; Guichelaar, Teun; van Baarle, Debbie; Koemans, Lotte; Berbée, Jimmy F. P.; Deboer, Tom; Meijer, Johanna H.; et al.
Abstract: Disruption of circadian rhythm by means of shift work has been associated with cardiovascular disease in humans. However, causality and underlying mechanisms have not yet been established. In this study, we exposed hyperlipidemic APOE*3‐Leiden.CETP mice to either regular light‐dark cycles, weekly 6 hours phase advances or delays, or weekly alternating light‐dark cycles (12 hours shifts), as a well‐established model for shift work. We found that mice exposed to 15 weeks of alternating light‐dark cycles displayed a striking increase in atherosclerosis, with an approximately twofold increase in lesion size and severity, while mice exposed to phase advances and delays showed a milder circadian disruption and no significant effect on atherosclerosis development. We observed a higher lesion macrophage content in mice exposed to alternating light‐dark cycles without obvious changes in plasma lipids, suggesting involvement of the immune system. Moreover, while no changes in the number or activation status of circulating monocytes and other immune cells were observed, we identified increased markers for inflammation, oxidative stress, and chemoattraction in the vessel wall. Altogether, this is the first study to show that circadian disruption by shifting light‐dark cycles directly aggravates atherosclerosis development.